Acinic cell carcinoma of parotid with predominant follicular pattern mimicking follicular neoplasm of thyroid - Lakshmi, A. Bhagya; Reddi, Bhavani Rao; Begum, Shaik Ayeesha; Devi, P. Urmila (International Journal of Research in Medical Sciences, 2017)
Acinic Cell Carcinoma (ACC) was previously called acinic cell tumor and it is a neoplasm demonstrating cytological differentiation towards serous acinar cells. The histological architecture of ACC is diverse and classification consists of various histological subtypes. This is a case of acinic cell carcinoma of parotid gland in a 45 years female patient which showed predominant follicular variant of ACC. It is a least frequent variant of ACC occurring in only 5% and it mimics follicular neoplasm of thyroid.